2012
DOI: 10.1002/jcop.21506
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Formal Versus Informal Sport: Mapping the Differences in Sense of Community

Abstract: As the popularity of sport continues to grow, more community developers, planners, and leaders are recognizing the ability for sport to foster community. Similar to other community contexts, understanding the structure and management of sport remains central to community building. Therefore, the aim of this study is to explain how sport system structural variations affect the sense of community experienced by those in and around sport. Eight focus groups were conducted with 39 sport participants from both form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 42 publications
0
53
0
Order By: Relevance
“…athletes. In particular, work by Warner, Dixon, and Chalip (2012), and Warner et al (2013) demonstrated a sense of community benefits both individuals and organizations. After extensive interviews and focus groups with 80 athletes, the summation of 2013a) work generated a Sport and Sense of Community theory.…”
Section: Sport Volunteerism and Sense Of Communitymentioning
confidence: 99%
See 2 more Smart Citations
“…athletes. In particular, work by Warner, Dixon, and Chalip (2012), and Warner et al (2013) demonstrated a sense of community benefits both individuals and organizations. After extensive interviews and focus groups with 80 athletes, the summation of 2013a) work generated a Sport and Sense of Community theory.…”
Section: Sport Volunteerism and Sense Of Communitymentioning
confidence: 99%
“…Given previous literature on sport volunteering (e.g., Coyne & Coyne, 2001;Farrell et al, 1998;Hamm, MacLean, & Misener, 2008) and sense of community and sport (e.g., Warner et al, , 2012Warner et al, , 2013, it is clear that social factors are important in sport volunteerism. Sport event volunteers typically receive training and/or orientation prior to the event.…”
Section: Sport Volunteerism and Sense Of Communitymentioning
confidence: 99%
See 1 more Smart Citation
“…While previous research has primarily focused on the mechanisms that create a sense of community (e.g. Pretty and McCarthy 1991;Warner et al 2012b) it would advantageous to also explore the factors that prevent a sense of community from forming. Thus, studying these destructive factors from a disenfranchised and marginalized perspective offers a broad perspective and is important for future research to consider.…”
Section: Female Officials 28mentioning
confidence: 99%
“…These findings are consistent with research that indicated both informal and formal settings can foster sense of community. Informal sport has also shown to advance sense of community characteristics (Warner, Dixon & Chalip, 2012). The findings are relational to the YPNG in that the organizations offers formal (professional development, volunteering) events, informal (mixers, hikes) events, and informal sports such as softball, beach volleyball and kickball tournaments.…”
Section: Discussionmentioning
confidence: 94%